Rural Green Financing for Energy Transition : Confronting Challenges In Village-Based Implementation - Indria Wahyuni; Sujatmoko, Emanuel; Prihatiningtyas , Wilda; Pramudita, Deah Ajeng (Faculty of Law, Universitas Pekalongan, 2025)
Indonesia’s target of achieving net-zero emissions by 2060 requires a massive energy transition, which must be implemented starting at the village level. Green energy independence at the village level will significantly contribute to the national energy mix target. Given that the energy transition entails a substantial financial burden, private sector participation is imperative. Green bonds have emerged as a viable financing instrument, with Village-Owned Enterprises serving as strategic entities for implementation. This study examines the challenges of accessing green financing to strengthen village capacity in undertaking energy transition initiatives. Employing a normative juridical approach—encompassing statutory, conceptual, and comparative analyses—the research highlights the critical role of green bonds, as one of the key financial mechanisms, in advancing village-based energy transition. The findings indicate that while green bonds are recognised as an important financing tool, their legal framework remains underdeveloped, thereby limiting their potential as an effective instrument of green financing